Enzyme Immobilization: Enhanced Enzyme Activity through Scaffolding on Customizable Self‐Assembling Protein Filaments (Small 20/2019). Issue 20 (17th May 2019) - Lim, Samuel; Jung, Gi Ahn; Glover, Dominic J.; Clark, Douglas S.
Abstract : In article number1805558, Douglas S. Clark and co‐workers report a versatile scaffolding platform based on a self‐assembling filamentous protein, gamma‐prefoldin (γ‐PFD), that can immobilize enzymes in a customizable fashion. The scaffold attachment can position fluorescent proteins in nanometer proximity or enhance the intrinsic catalytic activity of the immobilized enzymes.